Maximizing Seed Quality and Seed Yield of Bread Wheat (Tritium aestivum L.) Through Agronomic Management in Amhara Region, Northwestern Ethiopia - Derebe, Bitwoded; Assefa, Alemayehu; Abate, Alemu; Anbes, Tilaye (Journal of Tropical Crop Science, 2022)
A study was conducted to determine the optimum seed rate and row spacing on Kekeba bread wheat seed yield and quality performance at Adet and Wonberema, Ethiopia. The study consists of field experiments that were conducted at Adet Research Center and Wonberema farmer’s field during the 2018 and 2019 cropping seasons, and laboratory experiments at the Seed Science Laboratory at Adet Research Centre. A factorial combination of eight seed rates (75, 100,125, 150, 175, 200, 225, and 250 kg.ha-1) and two-row spacing (20 cm and 30 cm) was arranged in a randomized complete block design with three replications, and laboratory experiment in a complete randomized design with four replications. The results showed that the interaction effect of seed rate and row spacing was significantly (P<0.05) affected seed yield but had non-significant (P>0.05) on physical quality, physiological, and seedling vigor. Seed rate and row spacing had a significant (P<0.05) effect on standard germination, speed of germination, vigor index-I, and vigor index-II, but a pure seed was not significantly affected by the main effects and interaction. Based on the economic analysis at Adet, the maximum seed yield (4.4 t.ha-1) was obtained from a seed rate of 125 kg.ha-1 with 20 cm row spacing, and at Wonberema the maximum seed yield (3.26 or 3.17 t.ha-1) were obtained from a seed rate of 150 or 125 kg.ha-1 with 30 cm row spacing. Therefore, a seed rate of 125 kg.ha-1 with 20 cm row spacing was recommended at Adet, and at Wonberema seed rates of 150 and 125 kg.ha-1 with 30 cm row spacing was recommended for high seed yield and quality seed production as the 1st and the 2nd options, respectively.